Optical polarization study in the Centaurus Region: NGC 5662 - Vergne, María Marcela (2018)
We present (BV RI) multicolor linear polarimetric data of 73 of the brightest stars in the open cluster NGC 5662. Our objective is to study the characteristics of the interstellar medium (ISM) towards it and in its the environment. NGC 5662 is polarimetrically characterized by PV = 2.27%±0.13 and θV =89º.6 ± 1.17. Its polarization efficiency is much higher than the normal efficiency of ISM. The observed visual polarization in NGC 5662 is caused at least by three components of dust at ≈ 200 pc, 500 pc and 900 pc from the Sun. These have different polarimetric characteristics and the layer located at 500 pc has a variable density. The absorption presents a different behavior to polarization as the distance increases. A few of the observed stars present evidences of intrinsic polarization.